The Effect of Pregnancy-Related Anxiety on Prenatal Attachment in pregnant women with preeclampsia - Duman, Mesude; Yüksekol, Özlem Doğan; Ozan, Yeter Durgun (T.C. Sağlık Bakanlığı Ankara Şehir Hastanesi, 2021)
Aim: This study aimed at determining the relationship between the pregnancy related anxiety and prenatal attachment in pregnant women with preeclampsia. Materials and Method: This descriptive study, was conducted in the obstetric polyclinics of a university hospital in the Eastern Turkey. The study was conducted on 121 pregnant women with preeclampsia. The Descriptive Properties Form, Pregnancy Related Anxiety Questionnaire-R2 and Prenatal Attachment Inventory were used in data collection. Results: In the study, it was determined that educational level, pregnancy related anxiety, severity of preeclampsia and parity were important predictors for the prenatal attachment (R=0.624, R2=0.389, F=18.458, p

Amaç: Bu araştırma, preeklampsili gebelerde gebelik anksiyesitesi ile prenatal bağlanma arasındaki ilişkiyi belirlemek amacıyla yapılmıştır. Gereç ve Yöntem: Tanımlayıcı nitelikte tasarlanan bu araştırma Türkiye’nin doğusunda bulunan bir Üniversite Hastanesi Kadın Doğum polikliniklerinde yürütülmüştür. Araştırma toplam 121 preeklampsili gebe ile yapılmıştır. Verilerin toplanmasında Tanıtıcı Özellikler Formu, Gebelik Anksiyete Ölçeği ve Prenatal Bağlanma Envanteri kullanılmıştır. Bulgular: Araştırmada eğitim durumu, gebelik anksiyetesi, preeklampsi düzeyi, gebelik sayısının prenatal bağlanma için önemli yordayıcılar olduğu tespit edilmiştir (R=0.323, R2=0.105, F=11.313, p
Preeklampsili Gebelerde Gebelikle İlişkili Anksiyetenin Prenatal Bağlanmaya Etkisi
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi